Correction: Metal salt assisted electrospray ionization mass spectrometry for the soft ionization of GAP polymers in negative ion mode. Issue 7 (4th March 2020) - Muyizere, Theoneste; Zheng, Yajun; Liu, Hongni; Zhao, Jia; Li, Jin; Lu, Xianming; Austin, Daniel E.; Zhang, Zhiping
Abstract : Correction for 'Metal salt assisted electrospray ionization mass spectrometry for the soft ionization of GAP polymers in negative ion mode' by Theoneste Muyizere et al., Analyst, 2020, 145, 34–45.